Qualifications of science instructors in some selected teacher training institutions in the Philippines and their expressed role as teacher educators - Nakarmi, Sanu Man 1937- ([Quezon City s.n.], 1966)
This study analyzed the qualifications and the expressed role of science instructors. The author looked into previous work experiences, present teaching and laboratory assignment, in-service training activities, professional activities, objectives of science teaching, and methods of science teaching of science instructors.
Thesis (M.Ed.)--University of the Philippines
Keywords: Science teachers; Science -- Study and teaching -- Philippines